Compensa correr o risco de arriscar viver no clima portuense? Ou será um perigo para a saúde que devemos evitar? - Monteiro, Ana (2013)
To create efficient warning systems and prevent the health negative risks during extreme thermal events it is essential to know the local climate context to which humans are adapted. This adaptation includes the familiarization to a certain pattern of temperature variation and the expectations memorized but also, the individual characteristics of human beings (age, genetics, health, etc.), and the living conditions (housing, literacy, job, income, etc.). Having this puzzle in consideration and after analysing the relationships between temperature and mortality and morbidity in the Porto metropolitan area, since 2002 till 2007, it seems worthwhile to trigger the climatic risk prevention systems for the health of Porto's citizens in the case of extreme heat events since the 70th percentile (P70: Tmin > and Tmax > 15ºC and 25ºC), and in the case of extreme cold below the 30th percentile (P30: Tmin < 5ºC and Tmax < 13ºC). And these two elements - minimum and maximum temperature - should be considered at the same time as in the case of extreme heat or extreme cold they are equally important. The nocturnal contexts, given the fragile insulating conditions of artificial envelopes at Porto where people live indoor are as important as daily environment.